Clinicopathological Correlation in Asian Patients with Biopsy-Proven Lupus Nephritis. (19th March 2015) - Satirapoj, Bancha; Tasanavipas, Pamila; Supasyndh, Ouppatham
Abstract : A total of 244 patients with lupus nephritis (219 women (89.8%) with a female to male ratio of 9 : 1) were included in the study. Clinical and laboratory findings at renal biopsy are clinically valuable in identifying different renal classifications of lupus pathology, activity, and chronicity index. Patients with class IVG had significantly higher proportions of microscopic hematuria, proteinuria, hypertension, impaired renal function, anemia, hypoalbuminuria, and positive anti-DNA antibody. All of these findings correlated well with high activity index and chronicity index of lupus pathology. Considering these correlations may help to determine the clinicopathologic status of lupus patients.